Construction and characterization of a reporter gene cell line for assessment of human glucocorticoid receptor activation - Novotna, Aneta; Pavek, Petr; Dvorak, Zdenek (European journal of pharmaceutical sciences, 2012)
Glucocorticoids are widely used drugs in human pharmacotherapy. There is an increasing demand for tools allowing detection of the ligands for glucocorticoid receptor (GR), with regard to pre-clinical drug testing and environmental applications. We constructed human luciferase reporter gene cell line AZ-GR derived from HeLa human cervix carcinoma cells, which were stably transfected with reporter plasmid containing three copies of glucorticoid response element (GRE) upstream of luciferase reporter gene. We isolated five dexamethasone-responsive clones, and we further characterized two most responsive ones (AZ-GR). Dose-response analyses were performed with 22 different natural and synthetic steroids and the values of EC(50) were calculated. AZ-GR cells displayed high specificity and sensitivity to glucocorticoids, very low responsiveness to mineralocorticoids, but no responsiveness to estrogens, gestagens or androgens. Time-course analyses revealed that AZ-GR cells allow detection of GR activators soon after 14 h of the treatment (6-10-fold induction by 100 nM dexamethasone). Functionality of AZ-GR cells was not affected with cryopreservation. Generated reporter gene cell lines fully maintained responsiveness to glucocorticoids for 32 days in the culture and over 16 passages without significant alterations. The sensitivity of the assay allows high throughput format using 96-well plates. Collectively, we present here glucocorticoid-responsive stable reporter gene cell line that allows high throughput, rapid, sensitive and selective detection of GR activators, with possible use in pre-clinical research and environmental applications.
Keywords: steroidy; rychlé screeningové testy; Humans; HeLa buňky; Luciferases; luciferasy; lidé; HeLa Cells; High-Throughput Screening Assays; receptory glukokortikoidů; reportérové geny; Receptors, Glucocorticoid; Steroids; Genes, Reporter; glukokortikoidy; Glucocorticoids